2009
DOI: 10.1111/j.1475-1305.2008.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Residual Stresses with Optical Techniques

Abstract: The goal of this work is the development of other experimental techniques to measure residual stresses, as alternative to the hole-drilling method with strain gages. The proposed experimental techniques are based on the use of Moiré Interferometry and in-plane Electronic Speckle Pattern Interferometry (ESPI). Both are field techniques allowing the assessment of in-plane displacements without contact and high resolution. Grating replication techniques were developed to record high quality diffraction gratings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The validation of these results was carried out and was presented by Ribeiro et al. [24]. One example of the measurements performed is presented in Figure 5.…”
Section: Validation Of Experimental Measurementsmentioning
confidence: 90%
“…The validation of these results was carried out and was presented by Ribeiro et al. [24]. One example of the measurements performed is presented in Figure 5.…”
Section: Validation Of Experimental Measurementsmentioning
confidence: 90%
“…12. In 2009, Ribeiro et al [90] reported the results of a comparative study of ESPI and Moire interferometric methods applied with hole drilling to find residual stresses. For both approaches, worst case discrepancies with known stresses were approximately 15%, with most discrepancies on the order of 5%.…”
Section: Espimentioning
confidence: 99%
“…The optical speckle technique has evolved into a powerful tool for the measurement of surface strains since digital signal processing hardware and software have become widely available nowadays [3, 4, 5, 6]. It has the advantage that virtually no surface preparation is required, it works well for various surface structures and roughness and has high resolution [7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%